2022
DOI: 10.3390/genes13081356
|View full text |Cite
|
Sign up to set email alerts
|

PHEXL222P Mutation Increases Phex Expression in a New ENU Mouse Model for XLH Disease

Abstract: PhexL222P mouse is a new ENU mouse model for XLH disease due to Leu to Pro amino acid modification at position 222. PhexL222P mouse is characterized by growth retardation, hypophosphatemia, hypocalcemia, reduced body bone length, and increased epiphyseal growth plate thickness and femur diameter despite the increase in PHEXL222P expression. Actually, PhexL222P mice show an increase in Fgf23, Dmp1, and Mepe and Slc34a1 (Na-Pi IIa cotransporter) mRNA expression similar to those observed in Hyp mice. Femoral oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 105 publications
0
1
0
Order By: Relevance
“…Studies have indicated that a new mouse model for XLH disease, induced by N-ethyl-N-nitrosourea (ENU) and carrying the PHEX L222P mutation, exhibits an overexpression of PHEX transcript and protein, resulting in a loss-of-function phenotype ( 21 ). However, our findings in the mutant (c.1985delA) rat model revealed reduced expression of PHEX mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that a new mouse model for XLH disease, induced by N-ethyl-N-nitrosourea (ENU) and carrying the PHEX L222P mutation, exhibits an overexpression of PHEX transcript and protein, resulting in a loss-of-function phenotype ( 21 ). However, our findings in the mutant (c.1985delA) rat model revealed reduced expression of PHEX mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…It contains 22 exons and encodes the phosphate-regulating neutral endopeptidase PHEX, a glycoprotein of 749 amino acids (NP_000435.3) that belongs to the type II integral membrane zinc-dependent endopeptidase family. The PHEX protein has a large extracellular C-terminal domain, which contains the active sites and glycosylation sites, a transmembrane domain, and an N-terminal cytoplasmic tail [26,27]. It is predominantly expressed in osteoblasts, osteocytes, cartilage, and odontoblasts, and in these cells, PHEX deficiencies impair the cellular trafficking, endopeptidase activity, and FGF23 signaling that, in turn, reduce renal phosphate reabsorption, resulting in abnormal bone mineralization and hypophosphatemia [7].…”
Section: Discussionmentioning
confidence: 99%